Faith-Based Organisation (Fbo) In Fragile States: Analysing The Humanitarian Aid Policies Of Malaysian Fbos In Gaza, Palestine - Ahsad Ahmad, Ferooze Ali (2022)
Less research priority is given to Faith-Based Organisation donors (FBOs) activity in Gaza. This involves the effort to dissect the faith element as a potential influencing factor to FBOs aid policies within the fragile state. The dominant research over the past 20 years has been on Western state based donors’ aid modalities after the Oslo agreement in 1993. Previous discourse highlighted the tight political and economic regulations by Western donors, which affected how aid is distributed and utilised by Palestinians. Studies also underscored the rather tense donor-recipient relationship arising from such an arrangement. To address the gap, a phenomenology in-depth qualitative research is conducted on seven FBOs from Malaysia or Malaysian Faith-Based Organisations (MFBOs) operating in Gaza. MFBOs culture towards Islamic altruism and their embraced Islamic aid financing practices are observed, explored and dissected. MFBOs policies are also analysed against the Fragile State Principles (FSPs).